Comparison on the effect of treatment and subculturing on shoot regeneration from shoot tip seedlings of Psidium guajava L. var. Beaumont - Abdullah, Tajul Afif; Abdul Aziz, Maheran; Abdul Rashid, Azmi; Saleh, Ghizan; Elhory, Suleiman Mohamed Ahmed; Panjaitan, Syaiful Bahri; Sajili, Mohammad Hailmi; Mohamad, Noor Muzamil (Institute of Biotechnology and Genetic Engineering, 2009)
An experiment was carried out in order to study the effect of treatment containing 0.5 and 1.0 mg/L 6-benzylaminopurine (BAP) and effect of subculture on percentage of shoot formation, number of shoot per explant and mean shoot height of shoot tip explant of Psidium guajava L. var. Beaumont. MS medium (Murashige and Skoog, 1962) was used with 30 g/L of sucrose and 7 g/L agar type 900. Shoot tips of elongated shoots were decapitated to abolish its apical dominance prior to sub-culturing was carried out to a fresh medium every 4 weeks. The increase in mean number of shoots per explant and the shoot height was observed for every subculture. Treatment 1.0 mg/L BAP in comparison to treatment 0.5 mg/L BAP showed higher mean number of shoot per explant per subculture whereas treatment 0.5 mg/L BAP showed higher mean shoot height per subculture. Data were analyzed using T-test until the fifth subculture.